HUBUNGAN LOGIKA, BAHASA, DAN BUDAYA - hidayatullah, diny (AN-NAS, 2017)
âAs creatures that can think, humans need the means of thinking. The means include language and logic. The intersection between logic, language, and culture exists in humans as the culprit. Humans use their logic to speak, and the language used as a communication tool will create a culture. Culture develops with the help of logic, so it can form new language as the development of existing language. Where there are humans it is certain that language and culture exist. Because of the subjects, as well as objects of language and cultured, are human. The relationship of logic, language, culture is a relationship of mutual influence and has a very close relationship. All three become a whole communication system, binding, and enable the work of a society. It is also an interaction system that enables a society to occur, be nurtured and sustainably. Language as a part of the culture is a factor that allows the formation of culture. Language is the most importantly in a culture. Good language, showing a good society culture. Humans are able to maximize the potential of logic, of course, will be able to speak and cultured good. Language is a reflection of the nations culture. Language shows the personality of the nation.â